The Effect of Auction Game on Students’ Understanding of Simple Past Tense - M. Fadhly Farhy Abbas; Risnawati Risnawati; Destina Kasriyati (ELT-Lectura, 2020)
The aim of this research was to investigate the effect of auction game on students’ understanding of simple past tense at the eighth grade of MTs. Jabal Nur Kandis. The population of this research was the second year students of MTs. Jabal Nur Kandis consisting of two classes which had 48 students. The sample of this research were VIII A (24 students) as experimental class 1 and VIII B (24 students) as experimental class 2. The researchers applied auction game variation 1 in experimental class 1 while; in experimental class 2 the researcher applied auction game variation 2. The data was the students’ scores in simple past tense taken from the post test. The data was analyzed by using Normality-test, Homogeneity-test, T-test and N-gain. After conducting this research, it was found that the result of n-gain average score in experimental class is 0.39. The Assimp.Sig (2-tailed) is 0.195. So the hyphothesis H01 was accepted and Ha1 is rejected. With the Assimp.Sig (2-tailed) >0.05 it meant there was no any significant effect of the implementation of Auction game (variation 1 and variation 2) on students’ understanding of simple past tense. In conclusion, there was no any significant effect of the implementation of auction Game on students understanding of simple past tense at the eighth grade of MTs. Jabal Nur Kandis. But, auction game can improve students’ understanding on simple past tense.